2018
DOI: 10.1007/s40653-018-0218-8
|View full text |Cite
|
Sign up to set email alerts
|

Community Violence and Associated Psychological Problems Among Adolescents in the General Population

Abstract: Based on a populational survey conducted among 1400 adolescents aged between 12 and 17 years old, the aim of this study is to assess the relationships between their community violence experiences and their psychological health (anger, depressive symptoms, and post-traumatic stress disorder symptoms). One MANOVA confirms that both boys and girls who report at least one incident of physical community violence present more psychological difficulties, especially anger. Subsequent MANOVAs show that anger intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…The prevalence of depressive symptoms was highest in individuals with a history of both physical and sexual violence. These results are similar to study findings in a range of settings [67‐70] and suggest that minimizing physical and sexual violence against youth could decrease depressive symptoms later in life. Unfortunately, interventions aimed at minimizing violence against youth, and the consequences of violence (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of depressive symptoms was highest in individuals with a history of both physical and sexual violence. These results are similar to study findings in a range of settings [67‐70] and suggest that minimizing physical and sexual violence against youth could decrease depressive symptoms later in life. Unfortunately, interventions aimed at minimizing violence against youth, and the consequences of violence (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps unsurprisingly, adolescents have been found to maintain a high level of vigilance and develop strategies to safely navigate violent neighborhoods (Teitelman, et al, 2010). Therefore, exposure to community violence can have long-term negative effects on adolescents' emotional and behavioral development (Dubé et al, 2018;Kennedy et al, 2010) as well as physical health. Indeed, a systematic review of works has revealed numerous types of physical health outcomes in children and adolescents exposed to community violence, including effects on respiratory health, cardiovascular health, immune functioning, hypothalamic-pituitary-adrenal axis functioning, sleep problems, weight issues, and other general health complaints (Wright et al, 2017).…”
Section: Exposure To Violence In the Communitymentioning
confidence: 99%
“…Violence experienced in the community and on TV can also been linked to negative outcomes. For example, studies have shown adolescents reporting at least one incident of physical violence from within their community had more psychological difficulties and lower well-being, including internalizing and externalizing problems, depression, risky sexual behaviors and substance abuse (Dubé et al, 2018;Hindin & Gultiano, 2006;Kennedy et al, 2010;Mohammad et al, 2015;Udell et al, 2017).…”
Section: Exposure To Violence and Well-beingmentioning
confidence: 99%
“…En su estudio, Valdez y colegas encontraron que las personas que han tenido experiencias de crimen pueden desarrollar síntomas o trastornos significativos como la ansiedad, la depresión y el estrés postraumático. Además, las personas expuestas a este tipo de violencia pueden normalizar estos métodos de relacionarse en el hogar, la escuela, la familia, o en la comunidad, adoptando conductas, creencias o estilos de vida violentas como algo normal (Copp et al, 2016;Dubé et al, 2018;Gudiño et al, 2011).…”
Section: Introductionunclassified